Electrical properties of thermal oxide scales on pure iron in liquid lead-bismuth eutectic. (November 2020) - Qiu, Jie; Han, Junsoo; Schoell, Ryan; Popovic, Miroslav; Ghanbari, Elmira; Kaoumi, Djamel; Scully, John R.; Macdonald, Digby D.; Hosemann, Peter
Highlights: Electrochemical Impedance Spectroscopy (EIS) was employed to investigate the impedance behavior of thermal-oxidized iron in liquid lead-bismuth-eutectic. The impedance of the oxide film increases with increasing oxidizing temperature, due to the formation of a thicker scale and fewer defects. Increasing the oxidation time at a constant temperature can reduce the defect concentration in the oxide film and improve the resistivity of the oxide scale in LBE. EIS is a promising in-situ method to investigate the electrical properties and integrity of the oxide scales in liquid LBE in real-time. Abstract: The impedance behavior of pre-oxidized iron in liquid lead-bismuth eutectic (LBE) at 200 °C is studied using electrochemical impedance spectroscopy. The structures and resistance of oxide grown on iron oxidized in air at different temperatures and durations are compared. The results show that the resistance of the oxide film increases with increasing oxidizing temperature, due to the formation of a thicker scale and fewer defects. At the same temperature (600 °C), increasing the oxidation time can also reduce the defect concentration in the oxide film and improve the impedance of the oxide scale in LBE.